1987
DOI: 10.1111/j.1439-0418.1987.tb01016.x
|View full text |Cite
|
Sign up to set email alerts
|

New sex attractants for male Lepidoptera (Coleophoridae, Gelechiidae, Momphidae, Oecophoridae, and Yponomeutidae) found by field screening in The Netherlands

Abstract: By screening 48 mono‐unsaturated alkenyl acetates with chain lengths of 10, 12, 13, 14, and 16 carbon atoms singly and in binary mixtures sex attractants were discovered for fourteen species of Lepidoptera: Coleophora frischella, C. vacciniella (Coleophoridae), Brachmia blandella, B. inornatella, Bryotropha galbanella, B. senectella, Chionodes electella, Gelechia sororculella, Monochroa tenebrella, Sophronia semicostella (Gelechiidae), Batrachedra pinicolella (Momphidae), Bisigna procerella, Pseudatemelia spp.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Coleophora deauratella is one of minimally eleven Coleophora species in the frischella group which is Palearctic in distribution (Landry & Wright, 1993). Within this group, sex pheromone chemistry is poorly known and sex attractants for only two species, C. mayrella (Priesner, 1987) and Coleophora frischella (Willemse et al., 1987), have been elucidated. Coleophora frischella males are attracted to a 1:1 ratio of Z 7‐12:OAc and Z 5‐12:OAc in The Netherlands (Willemse et al., 1987); the same pheromone components isolated from female C. deauratella gland extracts in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Coleophora deauratella is one of minimally eleven Coleophora species in the frischella group which is Palearctic in distribution (Landry & Wright, 1993). Within this group, sex pheromone chemistry is poorly known and sex attractants for only two species, C. mayrella (Priesner, 1987) and Coleophora frischella (Willemse et al., 1987), have been elucidated. Coleophora frischella males are attracted to a 1:1 ratio of Z 7‐12:OAc and Z 5‐12:OAc in The Netherlands (Willemse et al., 1987); the same pheromone components isolated from female C. deauratella gland extracts in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Within this group, sex pheromone chemistry is poorly known and sex attractants for only two species, C. mayrella (Priesner, 1987) and Coleophora frischella (Willemse et al., 1987), have been elucidated. Coleophora frischella males are attracted to a 1:1 ratio of Z 7‐12:OAc and Z 5‐12:OAc in The Netherlands (Willemse et al., 1987); the same pheromone components isolated from female C. deauratella gland extracts in this study. Coleophora deauratella and two other members of the frischella group, C. mayrella and C. trifolii , are pests of different species of clover (red and alsike, white and sweet clover, respectively) seeds and occur sympatrically in both their native and introduced ranges (Landry & Wright, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Admixture of the other acetate is necessary, either E9-, Z10-or E10-14:OAc. WILLEMSE et al (1987) have reported (@-9-tridecenyl acetate (E9-13:OAc) to be a sex attractant for males of B. galbanellu. Z9a n d E9-14:OAc are known to be attractive for three other species of the family Gelechiidae, B. senectella Z.…”
Section: Bryotropha Galbanella (Z)mentioning
confidence: 99%
“…Vials containing the experimental odorants were hung in the top of delta traps with a sticky bottom S. Voerman of 10 x 17 cm ( WILLEMSE et al 1987). In 1990 these traps were transparent and colorless, while in the years before they were white opaque.…”
Section: Methodsmentioning
confidence: 99%
“…While in a field screening experiment in 1985 the mono-unsaturated compound (E)-4dodecen-1-01 acetate (E4-12:Ac) also appeared to be attractive for this species, the relative attractancy of E4-12:Ac and EZ4,7-13:Ac were not compared ( WILLEMSE et al 1987). In 1986, 1987, and 1990 the value of E4-12:Ac as a simple sex attractant for L. corylifoliella was tested in more detail and in competition with EZ4,7-13:Ac in a dune area and an apple orchard in The Netherlands.…”
Section: Introductionmentioning
confidence: 99%